Foundations of Russian Military Flight, 1885-1925 - Libbey, James K. (Naval Institute Press, 2019)
Foundations of Russian Military Flight focuses on the early use of balloons and aircraft by the Russian military. The best early Russian aircraft included flying boats designed by Dimitrii Grigorovich and large reconnaissance-bombers created by Igor Sikorsky.